Design of a release-free piezo-optomechanical quantum transducer - Paul Burger; Joey Frey; Johan Kolvik; David Hambraeus; Raphaël Van Laer (APL Photonics)
Quantum transduction between microwave and optical photons offers the potential to merge the long-range connectivity of optical photons with the deterministic quantum operations of superconducting microwave qubits. A promising approach to achieving this uses an intermediary mechanical mode along with piezo-optomechanical interactions. Traditionally, these transducers are suspended to confine mechanical fields, but this complicates manufacturing and comes with the major challenge of poor thermal anchoring and a trade-off between noise and efficiency. To overcome these issues, we introduce the—to our knowledge—first design of a release-free electro-optomechanical quantum transducer. Our release-free, i.e., non-suspended, design leverages a silicon-on-sapphire platform. It combines release-free lithium niobate electromechanical crystals with silicon optomechanical crystals on a sapphire substrate, optimizing thermal anchoring and microwave and mechanical coherence. Despite departing from the traditional suspended transducer paradigm, our release-free design achieves coupling rates sufficient for quantum-level interactions between microwave photons, phonons, and optical photons. Unconventionally, it utilizes high-wavevector mechanical modes tightly confined to the chip surface. Beyond quantum science and engineering, this platform and its design principles could also propel low-power acousto-optic systems in integrated photonics.